mathematical modelling and development of a monoball robot for educational purpose - M. H., Latif; H., Md. Yusof; Toha, Siti Fauziah (Universiti Putra Malaysia, 2016)
This paper introduces the development of a LEGO based self-balancing robot for the purpose of teaching fundamental concept of mechatronics subjects. This is a low cost and portable experimental assembly which would be suitable to introduce the important engineering subject such as control systems, embedded processors, programming and modelling.These subjects are thought towards the end of the programme and seldomly incorporated together. In this paper, the mathematical modelling of a self-balancing robot is proposed. This self-balancing robot has the capability of balancing itself on a ball which is based on the inverted pendulum theory. The design of the robot was made by first, analysing the dynamics of the inverted pendulum and from there on, a mathematical model is developed using free body diagrams. To add to the challenge of developing this robot for students, the mathematical model of the robot to be developed and modelled must be based on the spherical wheel inverted pendulum. The mathematical model is then verified by comparing the behaviour of the constructed robot with simulated model. The effectiveness of the PID and the LQR controller is verified by simulations and experimental results. Finally the usefulness of the self-balancing robot using LEGO Mindstorms and Arduino controller as a medium of teaching and learning mechatronics subjects is demonstrated.